Exploring Trends in Active Learning Methods Research: A Comprehensive Scopus-Based Bibliometric Study - Khanifah, Risda Mutik; Azani, Mohammad Zakki; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine the mapping of the development and direction of Active Learning Methods research in publications indexed by Scopus. This study used bibliometric analysis techniques to explore all journals indexed in Scopus' database of Active Learning Methods from 1985 to 2023. The data obtained were analysed using Excel and R/R-Studio. VOSviewer analyses the simultaneous occurrence of keywords and document citations visually. The author found 590 publications that fit the function, subject, and criteria set. The results of this study showed an annual growth rate of 10.96%, with the most publications on Active Learning Methods in 2022. The United States is the country that contributes the most publications, with an affiliation of the University of Florida. Rissanen became the most prolific writer on the theme of Active Learning Methods. The bibliometric analysis performed was limited to Scopus data. Other national and international databases should have been considered in the study. This study presents a brief overview of the literature accessible to researchers working in Education and provides recommendations for future research.